Optical characteristics and the linewidth enhancement factor measured from InAs/GaAs quantum dot laser diodes - Kim, Kyoung Chan; Han, Il Ki; Yoo, Young Chae; Lee, Jung Il; Sung, Yun Mo; Kim, Tae Geun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
We report the optical characteristics and the linewidth enhancement factor (a-factor) of InAs/GaAs quantum dot (QD) laser diodes (LDs) with a 5-mu m-wide stripe and 1-mm-long cavity. Continuous wave (CW) operation of the laser yielded a kink-free output power of 160 mW with an external efficiency of 0.35 W/A. The threshold current was 28 mA and the lasing occurred at 1286 nm, solely at the ground state (GS) up to a current of 345 mA, without switching to the excited state (ES). Then, to estimate the a-factor of the LDs, we investigated the differential gain and wavelength shift versus the current. The differential gain was 2.37 cm(-1)/mA at 1286 nm, and the wavelength shift was 0.00046 nm/mA, which resulted in an alpha-factor of 0.057 at 1286 nm. The a-factor decreased with increasing wavelength. To the best of our knowledge, this is the lowest value of the alpha-factor that has been reported so far, indicating that our QD-LD has excellent beam quality under high-power operation due to the elimination of the filamentation.
Keywords: ROOM-TEMPERATURE; SEMICONDUCTOR-LASERS; WELL LASERS; GAIN